Indirect comparison meta-analysis of two enoxaparin regimens in patients undergoing major orthopaedic surgery - Laporte, Silvy; Chapelle, Céline; Bertoletti, Laurent; Lega, Jean-Christophe; Cucherat, Michel; Zufferey, Paul J.; Darmon, Jean-Yves; Mismetti, Patrick; the META-EMBOL Group; on behalf of (Thrombosis and Haemostasis, 2014)
Two enoxaparin dosage regimens are used as comparators to evaluate new anticoagulants for thromboprophylaxis in patients undergoing major orthopaedic surgery, but so far no satisfactory direct comparison between them has been published. Our objective was to compare the efficacy and safety of enoxaparin 3,000 anti-Xa IU twice daily and enoxaparin 4,000 anti-Xa IU once daily in this clinical setting by indirect comparison meta-analysis, using Bucher’s method. We selected randomised controlled trials comparing another anticoagulant, placebo (or no treatment) with either enoxaparin regimen for venous thromboembolism prophylaxis after hip or knee replacement or hip fracture surgery, provided that the second regimen was assessed elsewhere versus the same comparator. Two authors independently evaluated study eligibility, extracted the data, and assessed the risk of bias. The primary efficacy outcome was the incidence of venous thomboembolism. The main safety outcome was the incidence of major bleeding. Overall, 44 randomised comparisons in 56,423 patients were selected, 35 being double-blind (54,117 patients). Compared with enoxaparin 4,000 anti-Xa IU once daily, enoxaparin 3,000 anti-Xa IU twice daily was associated with a reduced risk of venous thromboembolism (relative risk [RR]: 0.53, 95% confidence interval [CI]: 0.40 to 0.69), but an increased risk of major bleeding (RR: 2.01, 95% CI: 1.23 to 3.29). In conclusion, when interpreting the benefit-risk ratio of new anticoagulant drugs versus enoxaparin for thromboprophylaxis after major orthopaedic surgery, the apparently greater efficacy but higher bleeding risk of the twice-daily 3,000 anti-Xa IU enoxaparin regimen compared to the once-daily 4,000 anti-Xa IU regimen should be taken into account.
Keywords: Heparin / LMWH; meta-analysis; oral anticoagulants; orthopaedics; venous thrombosis